Degradation of the Environmental Pollutant Congo Red Dye through Adsorption and Photocatalysis Owing to the Exposure of CuS Nanoflowers - Sampa Mondal; Baibaswata Bhattacharjee (Journal of Water and Environmental Nanotechnology)
CuS nanoflowers are synthesized by employing a simple wet chemical method. The sample is characterized by its microstructural and optical properties. The sample shows significant absorption between 300 and 700 nm, followed by a quick reduction. This study is the first to show that a CuS nanoflower has an adsorption capacity to remove all moieties of Congo Red (CR), an environmental pollutant, in the dark. 100% dye removal of all CR dye moieties takes place in 52 min under darkness. The adsorption phenomena follow the Quasi-first-order kinetic model. The adsorption capacity for phenyl moiety is greatest. Additionally, 100% degradation of all CR dye moieties takes place in 24 min and 36 min in the presence of solar light, and white light, respectively. When comparing experimental settings (consecutively white light, and solar light), the change in degradation efficiency for the azo, naphthalene, and phenyl moieties with time is highest under solar light. The photocatalysis reactions follow pseudo-first-order kinetics according to the Langmuir-Hinshelwood (L-H) model. The degradation rate for all moieties of CR is more under solar light irradiation than under white light irradiation. However, the adsorption rate in the dark and the degradation rate in light for all CR moieties is enhanced due to the wide surface area of CuS nanoflowers. Additionally, the XRD pattern, FESEM image, and UV-Vis spectra do not show any significant change after the 6th cycle of the dye photodegradation study, suggesting that CuS nanoflowers are recyclable.